The Social Construction of Frivolity - Rodger A. Bates; Emily B. Fortner (Journal of Public and Professional Sociology)
Leisure is a continuum of behavior from normative to deviant. Some forms of leisure reflect widely shared cultural norms while others reflect only marginal or sub-cultural acceptance. Within this continuum, we label some harmless forms of non-traditional behavior frivolity. The social construction of frivolity is tempered by time, place, social class and tradition. In addition, frivolity can be a two-edged sword, defining the abnormal as normal or the normal as abnormal.